(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
"Imaginary space" in literature includes the area of the mind where characters’ thoughts, emotions, and inner conflicts reside. It’s a concept that allows authors to explore the psychological depths of their characters and convey complex themes and ideas. Narrators often play a crucial role in representing these imaginary spaces by providing insights into characters’ inner workings through introspective narration, inner monologues, and clear descriptions.